Announcements Effect of Corporate Bond Issuance on Stock Returns: Evidence from Chile - Cornejo-Saavedra, Edinson Edgardo; Muñoz Mendoza, Jorge Andrés; Delgado Fuentealba, Carlos Leandro; Sepúlveda Yelpo, Sandra María; Veloso Ramos, Carmen Lissette (Cuadernos de Administración, 2021)
This study measures the announcement effect of corporate bond issuance on stock returns for companies listed on the Santiago de Chile Stock Exchange (BCS). The sample is made up of 29 firms and 87 corporate bond issuance announcements during the 2010-2017 period. The announcement effect of corporate bond issuance on stock return is measured by an event study. This methodology allows to calculate abnormal returns for the days of the event period. The results show that the average abnormal return on the day of the announcement is negative (between -0.09% and -0.03%), but it is not statistically significant. However, the average abnormal return on the day after the announcement is positive (between 0.27% and 0.32%) and has statistical significance. The significant and positive average abnormal return on the day after the announcement suggests a late market reaction. The study shows that there is a significant signaling effect of bond issuance announcements on stock returns.